Contribution of Oxidative Stress and Inflammation to the Neurogenic Hypertension Induced by Intermittent Hypoxia - Oyarce, María P.; Iturriaga, Rodrigo (Frontiers in Physiology, 2018)
Chronic intermittent hypoxia (CIH), the hallmark of obstructive sleep apnea, is the main risk factor to develop systemic hypertension. Oxidative stress, inflammation and sympathetic overflow have been proposed as possible mechanisms underlying the CIH-induced hypertension. CIH potentiates the carotid body (CB) chemosensory discharge leading to sympathetic overflow, autonomic dysfunction and hypertension. Oxidative stress and pro-inflammatory molecules are involved in neurogenic models of hypertension, acting on brainstem and hypothalamic nuclei related to the cardiorespiratory control, such as the nucleus of the solitary tract, which is the primary site for the afferent inputs from the CB. Oxidative stress and pro-inflammatory molecules contribute to the activation of the CB chemoreflex pathway in CIH-induced hypertension. In this brief review, we will discuss new evidence for a critical role of oxidative stress and neuro-inflammation in development of the CIH-induced hypertension through activation of the CB chemoreflex pathway.